Loyalty among Collaborators at a Private Higher Education Institution: A Case Study in Celaya, Guanajuato - Luna Correa, Enrique José (2019)
This study analyzes the phenomenon of collaborator loyalty at a high school in the city of Celaya (Guanajuato). A literature review of previous related studies was first conducted, emphasizing Flores (2009) whose study, Loyalty within the Culture of Mexican Workers in  Mexico City, is used as a basis for this study. This phenomenon was addressed from a quantitative perspective, a correlational scope using a non, cross-cutting type experimental design. The hypothesis was that qualitative variables described as resources, team work, direct supervisor, senior administration and compensation influence satisfaction and loyalty. A document was used to measure the aforementioned variables, using a sample of 76 subjects who are also collaborators at the institution with a confidence interval of 95% and a margin of error of 3%. Lastly, the results were analyzed with the Kendall Tau-B correlational coefficient in order to prove the research hypothesis. The main finding was that the most significant variables that impact loyalty are teamwork, remuneration and compensation, which is empirical proof that can help the institution make decisions to increase loyalty from their collaborators. Controlling and stimulating teamwork, remuneration and compensations variables may significantly help increase collaborator loyalty. In addition, those results can be used as a baseline for other institutions to replicate the research models. In this manner, the results obtained can also help the decision-making process about desired collaborator loyalty values.